Conductive polymers and plastics in industrial applications - Rupprecht, Larry (Plastics Design Library ; Society of Plastics Engineers, 1999)
Materials and methods for electromagnetic interference (EMI), electrostatic discharge (ESD) and other electronics applications are covered in this book. Sections on material design, methods of manufacture and successful use of plastics containing conductive fillers, intrinsically conductive polymers and polymers utilizing new blending technology are included, and these technologies are compared to other methods such as metal plating. Chapters cover the effect of processing parameters and formulation on material performance.